1977
DOI: 10.4141/cjas77-061
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Laying Hens Fed Diets Containing Gums Derived From Tower Rapeseed

Abstract: laying hens fed diets containing gums derived from Tower rapeseed. Can. J. Anim. Sci.57: 479-483. An experiment was conducted to investigate whether rapeseed gums have any detrimental effect on the performance of laying hens. White leghorn pullets of a commercial strain were fed all-mash diets in which the major source of protein was provided by either soybean meal, rapeseed meal, rapeseed meal * 1.57o fapeseed gums, soybean meal -t 1.5Vo rapeseed gums or soybean meal + 1.57, soybean gums. Each diet was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1
1

Year Published

1978
1978
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
2
1
1
Order By: Relevance
“…However, when egg size was taken into account (kilogram of feed per kilogram of eggs), this difference disappeared, i.e., hens fed diets containing soybean gum consumed more feed but maintained a production rate similar to that of the control hens. These results are contrary to those of Leeson et al (1977), who reported that the addition of the gum had no effect on feed intake or egg production.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…However, when egg size was taken into account (kilogram of feed per kilogram of eggs), this difference disappeared, i.e., hens fed diets containing soybean gum consumed more feed but maintained a production rate similar to that of the control hens. These results are contrary to those of Leeson et al (1977), who reported that the addition of the gum had no effect on feed intake or egg production.…”
Section: Resultscontrasting
confidence: 99%
“…In a study carried out by Hulan & Proudfoot (1981), hens fed diets containing soybean gum consumed more feed but maintained a production rate similar to that of the control hens; however, the addition of this by-product had no effect on the specific gravity and interior quality of eggs. Leeson et al (1977) reported that the inclusion of the gum had no effect on feed intake or egg production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bu rafinerizasyon artığı glikolipitler, fosfolipitler ile değişik miktarda trigliserit, sterol ve yağ asitlerinden oluşmaktadır. RafinerİL:asyon artığının rasyonlaı a % 6'ya kadar ilave edilmesinin etlik piliçlerde ve yumurta tavuklarında hiçbir zararlı etki yapmadığı bildirilmektedir (7,10).…”
Section: Kolm Tohumunda Bulunan Glukosinolatlarınunclassified